Acute Abdomen in 8-year Old Girl due to Bilateral Ovarian Burkitt’s Lymphoma, Mwanza Tanzania: A Case Report (Tanzania Medical Journal, 2015)
Burkitt’s lymphoma is a highly aggressive lymphoma composed of monomorphic medium size B cells. It is endemic in Equatorial Africa presenting as a jaw or orbital tumor unlike sporadic Burkitt’s lymphoma which commonly presents with an abdominal tumor usually in the ovary. The presentation of the abdominal tumor sometimes can lead to challenges in clinical diagnosis, especially when it presents like an acute abdominal condition. This is a case report of an 8-year old female who was admitted at Bugando Medical Center with history of on and off abdominal pain and fever for two weeks. Physical examination revealed asymmetrical distended abdomen with a tender mass in the right iliac fossa and mild pallor. Presumptive diagnosis of appendicular mass was made with differential diagnosis of ovarian mass. Pelvic scan showed bilateral iliac masses suggestive of inflammatory process. At Laparotomy both ovary had a mass and bilateral salphingo-oophorectomy was done. The histopathology results showed ovarian Burkitt’s lymphoma. The patient had stage IV disease and chemotherapy treatment was started, however she died after the third course of chemotherapy. Although ovarian Burkitt’s lymphoma is common, presentation with signs of acute abdomen with involvement of both ovaries is not a usual mode of presentation.